CITIZEN PARTICIPATION IN RECYCLING COOKING OIL TO FOSTER A CIRCULAR ECONOMY PROGRAM - Muhammad Lukman Baihaqi Alfakihuddin; Aprila Paratih (SEAN Institute, 2022)
5000 to 15000 liters of used cooking oil contaminate soil and water. The cooking oil is wasted in the water flow and settles on the ground. Therefore, it is needed to overcome environmental problems. Citizen participation is required to support the circular economy program to overcome environmental issues. This study aims to investigate the used Cooking Oil and identify stakeholders who will play a role in supporting the recycling of used Cooking Oil. This qualitative research involves collecting and analyzing non-numerical data to understand concepts, opinions, or experiences. The results of this study are 1. Most of the citizens still throw the used cooking oil in inappropriate places 2. Seven stakeholders are needed to support Citizens in Participation in Cooking Oil Recycling: Palm Oil Industries, Biofuels Industries, Eco-Rewards, Collectors, Social Media campaigns, Head of RT, and national and local Government regulators. The collaboration among the stakeholders will determine the success of the recycling program. In addition, this research contributes to the knowledge base in nurturing citizen participation in a circular economy.